Inside-out versus standard artery graft to repair a sensory nerve in rats - de Castro Rodrigues, Antonio; Pai Silva, Maeli Dal [UNESP] (Wiley, 2001)
It is known that a vein graft provides a good microenvironment for axon regeneration in motor peripheral nerves, but the use of artery graft for regeneration of sensory nerves is controversial. We sectioned the saphenous nerve and repaired it by using heterologous inside-out and standard artery graft techniques in rats, After 4, 12, and 20 weeks, the graft and the distal stump were observed under electron microscopy. In each period studied, the pattern, diameters, and thickness of the myelin sheaths of the regenerated axons were measured in the graft and distal stump. There was capillary invasion in both the graft and distal stump, especially in the inside-out artery graft group. Regenerated nerve fibers were prominent in both heterologous artery grafts 4 weeks after the surgical procedures. Conversely, in the distal stump, regenerated nerve fibers were observed only after 12 weeks. In both the inside-out artery graft and standard artery graft, no statistical difference in the diameters and thickness of the myelinated fibers after 20 weeks was observed.